Fractal analysis of peri-implant trabecular bone complexity following transcrestal sinus floor elevation: a retrospective radiographic study - Irfan Ustundag; Sevval Ilkyaz; Numan Dedeoglu; Selman Bolukbasi; Mehmet Sait Simsek; Yunus Çetiner; Bahadir Sancar (Frontiers in Medicine, 2026)
Background This retrospective radiographic study aimed to evaluate time- and region-dependent changes in peri-implant trabecular bone structural complexity using fractal dimension analysis after transcrestal sinus floor elevation (TSFE) with 3, 4, or 5 mm sinus membrane elevation. Methods A total of 45 dental implants placed simultaneously with TSFE in 35 patients were categorized into three groups according to sinus membrane elevation height (3 mm, 4 mm, and 5 mm). Fractal dimension analysis was performed using ImageJ software on panoramic radiographs obtained at baseline and at 6 and 12 months postoperatively, in the apical, mesial, and distal peri-implant regions. Results No statistically significant difference was found among the 3 mm, 4 mm, and 5 mm groups in fractal dimension changes from baseline to 6 or 12 months postoperatively ( P > 0.05). In the 4 mm and 5 mm groups, no statistically significant temporal FD changes were detected in any region ( P > 0.05). In the 3 mm group, the distal fractal dimension value at 6 months was significantly lower than the apical value ( P = 0.006), whereas a significant increase was observed in the distal region between 6 and 12 months ( P = 0.013). Conclusion No statistically significant between-group differences in peri-implant trabecular bone structural complexity were detected among the 3 mm, 4 mm, and 5 mm TSFE groups over 12 months. These preliminary findings do not establish equivalence and require prospective confirmation; the transient distal change in the 3 mm group should be interpreted cautiously as a region-specific, hypothesis-generating observation.